Answer:
X is your answer bc when coordinates are flipped over the x-axis the y coordinate goes negative
Answer: x = -6
Step-by-step explanation: The problem gave us the y value, so we can just substitute it into the equation and solve it.
y = x - 6
y = 2x
2x = x - 6 (substitute the y value into the equation)
1x = -6 (subtract x on each side)
x = -6 (1x is basically saying x so you do not need to divide)
Answer:
See below.
Step-by-step explanation:
1. 3 * 15 + 4 * 15 - 5 * 15
45 + 60 - 75
105 - 75
30
2. 3x + 4x - 5x
7x - 5x
2x
3. 3(x-2) + 4(x-2) - 5(x-2)
3x - 6 + 4x - 8 - 5x + 10
2x - 4
4. (I'm not typing that out)
7.5x + 19.5 + 10x + 26 - 12.5x - 32.5
5x+13
-hope it helps
Answer:
222
Step-by-step explanation:
1114-5646